Development and application of a fiber2 protein-based indirect ELISA for detection of duck adenovirus 3. (December 2019) - Chen, Cuiteng; Wan, Chunhe; Shi, Shaohua; Cheng, Longfei; Chen, Zhen; Fu, Guanghua; Liu, Rongchang; Zhu, Chunhua; Huang, Yu
Abstract: Duck adenovirus 3 (DAdV-3) is a newly identified duck adenovirus that has recently emerged in China. The incidence of duck infection caused by this virus is very high, with very large economic losses to the poultry industry. Thus, there is an urgent need for a serological assay for the specific detection of DAdV-3. To this end, prokaryotic expression of the fiber2 protein of DAdV-3 was used as a coating antigen to establish an indirect enzyme linked immunosorbent assay (ELISA) method for the specific detection of antibodies against DAdV-3. The method was found to be specific, repeatable and more sensitive than the agarose gel precipitation test (AGP). This indirect ELISA method based on the recombinant fiber2 protein may be used for the clinical detection of DAdV-3 infection and for monitoring antibody levels after vaccine immunization and is of great significance for the effective prevention and control of the disease. Highlights: A fiber2 protein-based indirect ELISA was developed for newly identified duck adenovirus 3. The method is specific, repeatable and sensitive. The method can be used for clinical detection of duck adenovirus 3 infection and for monitoring antibody levels after vaccine immunization.